2008
DOI: 10.1089/tmj.2007.0032
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Technical Evaluation in Telemedicine Systems

Abstract: We conducted a systematic review of the literature to critically analyse the technical evaluation and assessment frameworks that have been applied to telemedicine systems. A total of 47 articles met the inclusion criteria. Subjective methods were predominantly used for technical evaluation (59%), e.g., Likert scale. Those including objective measurements (41%) were mainly restricted to simple metrics such as network time delays. Only 3 papers included a rigorous standards-based objective approach. Our investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…New networks, such as sensor networks, e-Health systems for patient monitoring [1] and social networks which promote human interaction, are producing data at a phenomenal rate. This data needs to be efficiently stored, processed and analysed.…”
Section: Introductionmentioning
confidence: 99%
“…New networks, such as sensor networks, e-Health systems for patient monitoring [1] and social networks which promote human interaction, are producing data at a phenomenal rate. This data needs to be efficiently stored, processed and analysed.…”
Section: Introductionmentioning
confidence: 99%
“…The interest in the potential of telemedicine to increase the quality, accessibility, utilisation, efficiency, and effectiveness of healthcare services is fuelled by the rapid development of information and communication technology (ICT) and connectivity [1]. The focus of this paper is specifically on the potential of telemedicine to strengthen hospital referral systems by reducing the need to transport patients between facilities [2].…”
Section: Introductionmentioning
confidence: 99%
“…20 One method of assessing feasibility is by reporting the amount of technical difficulties experienced to compare whether the number of difficulties has a negative impact on satisfaction rates, 12 as technical issues have been identified as one drawback to telemedicine that negatively affects care. 12,21 The predominant method by which to assess feasibility includes the use of surveys or questionnaires to measure satisfaction, which have been widely used in telehealth applications. 22 Surveys are an appropriate means to measure satisfaction because not only are they easily administered and not cumbersome for the respondent, 23 but they also provide valuable information into the perceptions of the individuals to whom the survey is targeted.…”
Section: List Of Tablesmentioning
confidence: 99%
“…In assessing technical issues related to systems in videoconferencing, Clarke and Thiyagarajan 21 conducted a systematic review to examine which elements needed to be addressed in a technical evaluation. 21 Using forty-seven articles in the review, nine of the articles dealt with business industry using videoconferencing while the other thirty-eight were related to telehealth. 21 They found that of these forty-seven articles reviewed, twenty-two of the studies used subjective measures to assess the technical evaluation, and over half of these subjective measures (59 percent) used Likert scales and questionnaires to evaluate the technical issues.…”
Section: Measuring Feasibility: Technical Difficultiesmentioning
confidence: 99%
See 1 more Smart Citation